2021
DOI: 10.1371/journal.pgph.0000016
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and associated factors among undergraduates: A university-based cross-sectional study in Nepal

Abstract: Health literacy is one of the most critical aspects of health promotion. Limited health literacy is also accounted for adverse health outcomes and a huge financial burden on society. However, a gap exists in the level of health literacy, especially among undergraduates. This study aimed to assess the levels of health literacy and its socio-demographic determinants among undergraduate students of Tribhuvan University, Nepal. A web-based cross-sectional survey was conducted among 469 undergraduate students from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…Male adolescents had lower odds of having limited reproductive health literacy compared to their female counterparts (AOR = 0.48, 95% CI: 0.26, 0.88). Even though comparable literature is lacking speci c to reproductive health literacy, the present nding is supported by previous studies [31,32], which reported higher odds of limited health literacy among female participants.…”
Section: Discussionsupporting
confidence: 88%
“…Male adolescents had lower odds of having limited reproductive health literacy compared to their female counterparts (AOR = 0.48, 95% CI: 0.26, 0.88). Even though comparable literature is lacking speci c to reproductive health literacy, the present nding is supported by previous studies [31,32], which reported higher odds of limited health literacy among female participants.…”
Section: Discussionsupporting
confidence: 88%
“…The finding regarding lower monthly income as predictor of low literacy is consistent with the results of some studies conducted among university students (Zhang et al, Evans et al, Svendsen et al, Bhusal et al). 11,12,14,17 In the contrary, health literacy was not associated with parent's highest level of education as reported in previous studies. 11,14,[18][19][20] This contrast observation is not well understood and needs to be explored prospectively in future research.…”
Section: Discussionsupporting
confidence: 51%
“…The reason behind the reflection of such reverse scenario might be the difference in study settings as the countries are rich enough in order to the economic development levels, health resource allocations, and access to health information compared to Bangladesh (majority of the respondents had monthly family income less than 40000 BDT), Ghana and Nepal. 11,12 However, the contrast observation reported in the similar studies conducted among the Dutch adults and the Turkish university students, where females were found to have better literacy rather than male. 14,15 As Bangladeshi citizens belong the patriarchal culture where males tend to have all the fundamental opportunities dominantly rather than female, that's why such disproportions might be attributed in this study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…e undergraduate stage is crucial as it is the transition period from teenager to young adult, moving out of home and relying less on parents to make daily life decisions. It is usually seen that risk-taking behaviors begin to manifest during this stage [3,[6][7][8]. Also, college students are easy targets for the tobacco industry; young people like them are bombarded with protobacco messages and sometimes offered free tobacco products [8].…”
Section: Introductionmentioning
confidence: 99%